Studi Konsumsi Energi di Kantin Keluwih Universitas Surabaya - Irawati, Fenny; Kartikasari, Fitri Dwi (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2021)
Abstract—A study of energy consumption in the Keluwih canteen at the University of Surabaya (UBAYA) has been conducted as a first step to determine the design of the use of alternative energy that is appropriate in the canteen. The study began with conducting an energy consumption survey in the Keluwih canteen to find out the energy needs in the canteen. This energy consumption is measured by the energy used for lighting (lamps), air conditioning (AC), and other electronic equipment (television, blenders, rice cookers, electric stoves, etc.) and fuel used for cooking. Data were obtained from a questionnaire given to booth the canteen manager and tenants in the Keluwih canteen. From the data obtained, it can be knewn the energy consumption map in the Keluwih Canteen and based on the survey that has been done can be concluded that the energy consumption in the Keluwih Canteen is dominated by electricity which is around 600 kWh/day. Keywords: energy consumption, keluwih canteen, survey, questionnaire, electricity Abstrak—Telah dilakukan studi konsumsi energi di kantin Keluwih Universitas Surabaya (UBAYA) sebagai langkah awal untuk menentukan desain pemanfaatan energi alternatif yang tepat guna di kantin tersebut. Kajian diawali dengan melakukan survei konsumsi energi di kantin Keluwih untuk mengetahui kebutuhan energi di kantin. Konsumsi energi ini diukur dari energi yang dipergunakan untuk penerangan (lampu), pendingin ruangan (AC), dan peralatan elektronik lainnya (televisi, blender, rice cooker, kompor listrik, dll.) serta bahan bakar yang dipakai untuk memasak. Data diperoleh dari kuesioner yang diberikan kepada pengelola kantin serta penyewa stan di kantin Keluwih. Dari data yang diperoleh dapat diketahui peta konsumsi energi di Kantin Keluwih dan berdasarkan survei yang telah dilakukan dapat disimpulkan bahwa konsumsi energi di Kantin Keluwih didominasi oleh energi listrik yang jumlahnya berkisar 600 kWh/hari. Kata kunci: konsumsi energi, kantin keluwih, survei, kuesioner, energi listrik